The Effect of Emotional Social Development on Physical Motor Development in Early Childhood - Zara Mayra; Muhammad Nizar Maulana; Kushendar Kushendar (Journal of Childhood Development, 2022)
Social development is the development of behavior in children where children are asked to adapt to the rules that apply in the community. Emotional development will affect how children's attitudes and behavior towards the surrounding environment. so that the role of parents, peers, teachers and those around them is very important in supporting children's development, especially at an early age. This article used library reaserch method, from book, theory of pshycosocial and finding figure social emotional development. Finding of this discustions according to the literature review conducted, it was found that at an early age, which is around 4 to 6 years, is the most appropriate age to shape children's character by stimulating positive things to children and reducing the emergence of negative attitudes in children. Therefore, children at an early age need supervision, especially in bringing up the right stimulus to receive stimulation that is quite good, directed, and driven to the level of growth and development.